Understanding the Activity and Stability of Electrocatalytic Materials - Smiljanić, Milutin (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2024)
Climate change and environmental degradation, which are among the greatest concerns of the modern world, are directly linked to the ever-increasing use of fossil fuels. Electrochemistry and electrocatalysis have proven to be key factors in the transition to sustainable energy and clean chemical production. For example, the implementation of the hydrogen economy concept largely depends on the efficiency of water electrolyzers and fuel cells, which are used to produce green hydrogen and convert it into electricity without carbon emissions. In addition, electrochemical conversion processes offer promising opportunities to extract value-added chemicals from abundant CO2 and to produce ammonia through the electro-reduction of nitrogen. The efficiency of these electrochemical devices depends on the performance of the catalytic materials used to carry out the reactions. This talk will focus on investigating the stability and activity of electrocatalytic composites as two key factors for their applicability. The approaches developed for the in-depth investigation of the degradation processes of electrocatalytic materials based on the coupling of electrochemistry with advanced techniques such as electron microscopy and ICP-MS will be presented. The second part focuses on metal-support interaction (MSI) as an effective tool for tailoring advanced electrocatalytic composites. In contrast to carbon, advanced support materials (such as in-house developed titanium oxynitride) can induce MSI, which can enhance the activity and also the stability of supported metal nanoparticles for water-splitting reactions.